Telepathology - Kumar, Sajeesh; Dunn, Bruce E. (Springer Berlin Heidelberg : Imprint: Springer, 2009)
Developments in telepathology are progressing at a great speed. As a consequence, there is a need for a broad overview of the field. This first ever book on telepathology is presented in such a way that it should make it accessible to anyone, independent of their kno- edge of technology. The text is designed to be used by all prof- sionals, including pathologists, surgeons, nurses and allied health professionals, and computer scientists. In a very short time, driven by technical developments, the field of telepathology has become too extensive to be covered by only a small number of experts. Therefore, this Telepathology book has been written with chapter contributions from a host of renowned international authorities in telepathology (see the Table of Contents and the List of Contributors). This ensures that the subject matter focusing on recent advances in telepathology is truly up to date. Our guiding hope during this task was that as editors of multiple chapters we could still write with a single voice and keep the content coherent and simple. We hope that the clarity of this book makes up for any limitations in its comprehensiveness.